Birthweight z‐score and fat‐free mass at birth predict body composition at 3 years in Danish children born from obese mothers. (5th April 2022) - Berglund, Nanna R.; Lewis, Jack I.; Michaelsen, Kim F.; Mølgaard, Christian; Renault, Kristina M.; Carlsen, Emma M.
Abstract: Aim: We investigated associations between newborn body composition and anthropometry and body composition at 3 years in Danish children born from obese mothers. Methods: Analyses are based on data from the observational cohort study SKOT II (SKOT; small children's diet and well‐being (Danish)). Body composition at birth and at 3 years was assessed by dual‐energy X‐ray absorptiometry (DXA) scans and bioelectrical impedance analysis (BIA), respectively. Multiple linear regression models were applied to determine associations between newborn body composition and anthropometry and body composition at 3 years. Results: Birthweight z‐score (BWZ) was positively associated with fat‐free mass (FFM), height, fat‐free mass index (FFMI), fat mass (FM) and fat mass index (FMI) at 3 years. Newborn FFM was positively associated with FFM, height, FFMI and FM at 3 years, and positive trends were seen between newborn FM and FM and FMI at 3 years. Conclusion: We showed that infants born with a higher BWZ go on to be taller at 3 years. They also grow to be heavier, to which FM and FFM both contribute, independently of linear growth. Additionally, it seems that FFM tracks into early childhood, thus supporting intrauterine programming of later health.